2011
DOI: 10.1002/mabi.201000505
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Growth Factor Immobilization Strategies for Tissue Repair and Regeneration

Abstract: Growth factors play a critical role in regulating processes involved in cellular differentiation and tissue regeneration, and are therefore considered essential elements in many tissue engineering strategies. The covalent immobilization of growth factors to biomaterial matrices addresses many of the challenges associated with delivering freely-diffusible growth factors and has thus emerged as a promising method of achieving localized and sustained growth factor delivery. This Feature Article discusses methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(188 citation statements)
references
References 105 publications
4
179
1
1
Order By: Relevance
“…The bioactivity of growth factors presented in an immobilized form has also been shown in other studies, indicating that the release of the proteins and their subsequent internalization are not essential for cell stimulation 24,25 . In fact, the covalent immobilization of growth factors allows the sustained stimulation of the target cells while maintaining an effective dosage because of enhanced occupancy rate of different types of receptors at the cell membrane 22,23,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity of growth factors presented in an immobilized form has also been shown in other studies, indicating that the release of the proteins and their subsequent internalization are not essential for cell stimulation 24,25 . In fact, the covalent immobilization of growth factors allows the sustained stimulation of the target cells while maintaining an effective dosage because of enhanced occupancy rate of different types of receptors at the cell membrane 22,23,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, controlled release of growth factors has been investigated to sustain their effects for blood vessel formation. 38, 39 In scaffold-based tissue engineering, many researchers have incorporated growth factors in the polymer scaffolds. Growth factors are simply mixed within both hard porous materials, as well as soft gel materials, and biodegradation of the scaffold causes the slow release of the incorporated growth factors.…”
Section: Microfabrication Technologies For Fabricating In Vitro Vascumentioning
confidence: 99%
“…122 The presentation mode of GFs is a critical step for the generation of a specific tissue response, and several studies have focused on the evaluation of the effect of immobilization technique on cellular response. [123][124][125][126][127][128][129][130][131] For example, it is reported that soluble VEGF induces endothelial cell proliferation, while matrix-bound VEGF promotes vascular sprouting and branching 132 despite other studies revealing opposite responses. 86,130,133,134 Moreover, sustained activation of the Smad intracellular signaling pathway is stimulated upon culture of osteoblastic cells on immobilized BMP-2 due to prolonged phosphorylation of Smad 1/5/8 by In vivo critical-size defects.…”
Section: Single Gf Deliverymentioning
confidence: 99%
“…126 The combined release of BMP-2 and VEGF is commonly approached with mixed results, and control over amount and timing of GF delivery is critical. VEGF dosage must be tightly controlled as excessive amounts of this GF can inhibit osteogenesis and cause severe leakage and hypotension.…”
Section: From Single To Multiple Bioactive Factor Delivery For Skeletmentioning
confidence: 99%